Baya Weaver Ploceus philippinus (Linnaeus, 1766) nesting on Bottlebrush trees Callistemon in Jodhpur, Rajasthan, India - Kumar, Sanjeev; Kumar, Seema (Journal of the Bombay Natural History Society (JBNHS), 2015)
No Abstract.